Startup CEO : a field guide to scaling up your business - Blumberg, Matt (Startup revolution series., 2013)
A definitive book for any CEO-first time or otherwise-of a high-growth company While big company CEOs are usually groomed for the job for years, startup CEOs aren't-and they're often young and relatively inexperienced in business in general. Author Matt Blumberg, a technology and marketing entrepreneur, knows this all too well. Back in 1999, he started a company called Return Path, which later became the driving force behind the creation of his blog, OnlyOnce-because ""you're only a first time CEO once."" Now, more than a decade later, he's written Startup CEO. As the fif